V3+ extends the V3 framework to ensure user-centricity and scalability of sensor-based digital health technologies - Jessie P. Bakker; Roland Barge; Jacob Centra; Bryan Cobb; Chas Cota; Christine C. Guo; Bert Hartog; Nathalie Horowicz-Mehler; Elena S. Izmailova; Nikolay V. Manyakov; Samantha McClenahan; Stéphane Motola; et al. (npj Digital Medicine)
Abstract We propose the addition of usability validation to the extended V3 framework, now “V3+”, and describe a pragmatic approach to ensuring that sensor-based digital health technologies can be used optimally at scale by diverse users. Alongside the original V3 components (verification; analytical validation; clinical validation), usability validation will ensure user-centricity of digital measurement tools, paving the way for more inclusive, reliable, and trustworthy digital measures within clinical research and clinical care.